The Changing Profile of the Natural Law - Crowe, Michael Bertram. author. aut Link
321 p. 3 illus.
Keywords: It has more than once been observed that funeral orations for the natural law have always been premature. ! The implication that the concept has a continuing vitality, giving the lie to the prophets of its doom, is justification for yet another book on a subject, now as much as ever in the two and a half millenia of its history a matter of controversy. The history of the natural law has often been written -or at least the history of the concept in the Western European Greco 2 Roman tradition. This study does not claim to be a history, although its method is primarily historical and its subject is an idea that, more perhaps than most, has been shaped by its history. The omissions, Hobbes, Vico, Kant, Hegel for example, amply demonstrate that this is not a systematic history. On the other hand it accepts that In an orderly preparation for the study of natural law the most impor tant step would be to list the main modifications undergone by the notion of natural law as a result of doctrinal and historical cir cumstances? 1 Bergbohm, Jurisprudenz und Rechtsphilosophie, cited in a. M. Manser, Vas Natu"echt in Thomistischer Beleuchtung, p. 1; cf. A. P. d'Entreves, Natural Law, p. 13: "It was declared dead, never to rise again from its ashes. Yet natural law has survived and still calls for discussion. " 2 A.